The emerald berries - Green, Poppy; Bell, Jennifer (Jennifer A.), 1977- (New York : Little Simon, 2015)
Eight-year-old Sophie learns about some special emerald berries that will make the perfect color for a painting she wants to do, so she asks her friend Hattie to go with her to Weedsnag Way, a part of the forest that is far from home and very frightening.
Keywords: Fear -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Mice -- Juvenile fiction; Frogs -- Juvenile fiction; Squirrels -- Juvenile fiction; Animals -- Juvenile fiction